2007
DOI: 10.1016/j.devcel.2006.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dishevelled with the Clathrin AP-2 Adaptor Is Required for Frizzled Endocytosis and Planar Cell Polarity Signaling

Abstract: Upon activation by Wnt, the Frizzled receptor is internalized in a process that requires the recruitment of Dishevelled. We describe a novel interaction between Dishevelled2 (Dvl2) and micro2-adaptin, a subunit of the clathrin adaptor AP-2; this interaction is required to engage activated Frizzled4 with the endocytic machinery and for its internalization. The interaction of Dvl2 with AP-2 requires simultaneous association of the DEP domain and a peptide YHEL motif within Dvl2 with the C terminus of micro2. Dvl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
165
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(175 citation statements)
references
References 71 publications
10
165
0
Order By: Relevance
“…Dsh interacts with the clathrin AP-2 adaptor in part via its DEP domain and promotes endocytosis and degradation of Fz4 (27). Moreover, Wnt5a induces the formation of a complex between Dsh and the E3 ubiquitin ligases Smurf1 and Smurf2, promoting ubiquitination and degradation of Prickle, a cytoplasmic component of the non-canonical Wnt signaling pathway (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dsh interacts with the clathrin AP-2 adaptor in part via its DEP domain and promotes endocytosis and degradation of Fz4 (27). Moreover, Wnt5a induces the formation of a complex between Dsh and the E3 ubiquitin ligases Smurf1 and Smurf2, promoting ubiquitination and degradation of Prickle, a cytoplasmic component of the non-canonical Wnt signaling pathway (36).…”
Section: Discussionmentioning
confidence: 99%
“…Role of Dishevelled in Syndecan4 Steady-state Levels-Because Dsh interacts with SDC4 (16) and binds to components of the endocytic pathway (27,28), we decided to evaluate the role of Dsh in regulating SDC4 steady-state levels. In gain-of-function experiments we found that Dsh reduces SDC4 steady-state levels (Fig.…”
Section: Non-canonical Wnt Signaling Reduces Cell Surface Levels and mentioning
confidence: 99%
“…In cells that have induced and high levels of Dab2, such as RA-differentiated F9 cells, the Wnt signalosome is either not properly endocytosed and/or not properly assembled at the plasma membrane due to AP-2 sequestration. Interestingly, AP-2 and Dvl associations have recently be shown to be required for frizzled endocytosis (Yu et al, 2007). We have previously demonstrated that Dab2 can interact with Dvl and that Dab2 overexpression can disrupt Axin/ Dvl interactions (Hocevar et al, 2003).…”
Section: Dab2 and Wnt Signaling Y Jiang Et Almentioning
confidence: 97%
“…Direct binding of a polybasic stretch in the DEP domain to negatively charged lipids was recently shown to contribute to formation of the Fz-Dvl complex at the PM (30). In addition, the Dvl2 DEP domain, aided by a YHEL motif in the Dvl C terminus, interacts with μ2-adaptin, a subunit of the AP-2 clathrin adaptor complex, to facilitate clathrin-mediated endocytosis of Fz4 and Dvl2 on Wnt activation (31,32). Both of these activities of the DEP domain are mainly linked to PCP signaling, however, leaving the role of the DEP domain in β-catenin-dependent signaling unexplained (29,(33)(34)(35)(36).…”
mentioning
confidence: 99%